Cost-effectiveness of a new ACI technique for the treatment of articular cartilage defects of the knee compared to regularly used ACI technique and microfracture. (31st December 2023) - Snow, Martyn; Mandalia, Vipul; Custers, Roel; Emans, Pieter J.; Kon, Elizaveta; Niemeyer, Philipp; Verdonk, René; Gaissmaier, Christoph; Roeder, André; Weinand, Sina; Zöllner, York; Schubert, Tino
Abstract: Aims: For patients with cartilage defects of the knee, a new biocompatible and in situ cross-linkable albumin-hyaluronan-based hydrogel has been developed for matrix-associated autologous chondrocyte implantation (M-ACI) – NOVOCART Inject plus (Ninject; TETEC AG, Reutlingen, Germany). We aimed to estimate the potential cost-effectiveness of NInject, that is not available on the market, yet compared to spheroids of human autologous matrix-associated chondrocytes (Spherox; CO.DON GmbH, Leipzig, Germany) and microfracture. Materials and methods: An early Markov model was developed to estimate the cost-effectiveness in the United Kingdom (UK) from the payer perspective. Transition probabilities, response rates, utility values and costs were derived from literature. Since NInject has not yet been launched and no prices are available, its costs were assumed equal to those of Spherox. Cycle length was set at one year and the time horizon chosen was notional patients' remaining lifetime. Model robustness was evaluated with deterministic and probabilistic sensitivity analyses (DSA; PSA) and value of information analysis (VOIA). The Markov model was built using TreeAge Pro Healthcare. Results: NInject was cost-effective compared to microfracture (ICER: ₤5, 147) while Spherox was extendedly dominated. In sensitivity analyses, the ICER exceeded conventional WTP threshold of ₤20, 000 only when the utility value after successful first treatment with NInject was decreased by 20% (ICER: ₤69, 620). PSA corroborated the cost-effectiveness findings of NInject, compared to both alternatives, with probabilities of 60% of NInject undercutting the aforementioned WTP threshold and being the most cost-effective alternative. The VOIA revealed that obtaining additional evidence on the new technology will likely not be cost-effective for the UK National Health Service. Limitations and conclusion: This early Markov model showed that NInject is cost-effective for the treatment of articular cartilage defects in the knee, compared to Spherox and microfracture. However, as the final price of NInject has yet to be determined, the cost-effectiveness analysis performed in this study is provisional, assuming equal prices for NInject and Spherox.